Development of Open Ended Based Mathematics E-Modules to Enhance Students' Critical Thinking Ability - Purwoko, Riawan Yudi; Kusumaningrum, Betty; Laila, Annis Nur; Astuti, Erni Puji (Universitas Wiralodra, 2023)
In the current era of globalization, students' critical thinking skills are still low, so teaching materials that support learning are needed. In the learning process, educators have not developed teaching materials that are following technological advances, and existing teaching materials use more routine questions so that students only accept and follow the flow and rules rather than experimenting and finding answers or solutions on their own. Therefore, this study aims to produce an open-ended based mathematics e-module product on a system of two-variable linear equations for class VIII students of junior high school, to determine the feasibility of the product in terms of valid, practical, and effectiveness, to determine the increase in students' critical thinking skills after using e-module. This is development research with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at a Public Middle School in Purworejo for the 2021/2022 academic year. The data collection technique in this study was carried out through questionnaires and tests. The instruments used in this study were validation sheets, questionnaires, and tests. Data analysis techniques use validity, practicality, and effectiveness tests. The results of this study are open-ended-based mathematics e-modules to improve students' critical thinking skills. The product test results showed that the e-module validity score obtained a percentage of 80% from material experts and 82.5% from media experts. The results of the practicality test of the e-module obtained a percentage of 78% from the limited test and a percentage of 74% from the wide test. The results of the effectiveness of open-ended-based mathematics e-module products, namely the N-Gain test, obtained 0.6 in the medium category. The data shows that the e-module developed in this study is categorized as feasible. Students' critical thinking skills after using open-ended-based mathematics e-modules have increased.